CORPORATE SOCIAL RESPONSIBILITY, KEARIFAN LOKAL TRI HITA KARANA, DAN PARIWISATA BERBASIS MASYARAKAT BERKELANJUTAN - luh putu mahyuni; i gusti ayu agung tistha dewi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2021)
This study explores how Corporate Social Responsibility (CSR) based on local wisdom ‘tri hita karana’ are implemented to develop a sustainable community-based tourism. This study uses a qualitative case study approach conducted at Sangeh Monkey Forest (MF) tourism object. Data were obtained through in-depth interviews and then analyzed by using coding and themeing technique. This research indicates that Sangeh MF tourism object implemented CSR in three major areas, namely: 1. Social (people and ‘pawongan’ in ‘tri hita karana’); 2. Environment (planet and ‘palemahan’ in ‘tri hita karana’); 3. CSR related to business operation and religious activities (profit and ‘parahyangan’ in ‘tri hita karana’). CSR based on ‘tri hita karana’ principles were also implemented through participation of local community in managing the tourism object. All income generated from the operational of tourism object were given back to the community. The informant of this study perceived CSR as socially responsible business practices and as philanthropic actions. This research offers an insight into how CSR could be implemented based on local wisdom ‘tri hita karana’ to develop a sustainable community-based tourism object. Several recommendations on how to further improve CSR practices by integrating business, social, and environment goals are also offered.